Investigation of helical flow by using tracer technique - Hacıyakupoğlu S.; Karatepe N.; Baydoğan N.; Baytaş F.; A.B., Tuğrul; Altınsoy N.; Büyük B. (EDP Sciences, 2013)
The flow through coiled tubes is, in practice, important for pipe systems, heat exchangers, chemical reactors, mixers of different gas components, etc., and is physically interesting because of the peculiar characteristics caused by the centrifugal force. Therefore, it is not so easy to observe flow parameters in the helical pipe experimentally. Tracer techniques are being increasingly used to determine characteristics such as volume flow rate, residence time, dispersion and mixing process in industry. In this study, the flow in the helical pipe was obtained in the laboratory and investigated by using the tracer technique. The experimental system including the helical pipe was set up in the laboratory. In the experiments methylene-blue (C16H17N3S) has been used as the tracer. The experiments were successfully performed with different flow rates and their results were evaluated with the flow parameters.
Keywords: Physics; QC1-999